2017
DOI: 10.1108/jmtm-09-2015-0079
|View full text |Cite
|
Sign up to set email alerts
|

Configuration and options management processes and tools: an automotive OEM case study

Abstract: Purpose The purpose of this paper is to propose a three-staged approach to configuration change management that uses a combination of complexity analysis, data visualization, and algorithmic validation to assist in validating configuration changes. Design/methodology/approach In order to accomplish the above purpose, the authors conducted a review of existing configuration management practices. This was followed by an in-depth case study of the configuration management practices of a major automotive OEM. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…The new view on ECs is timely, as, across manufacturing industries, there has been a widespread shift in the approach to manufacturing, from mass production to mass customization [32]. This new approach has been embraced by manufacturers because of the need to make continuous improvements in order to create competitive products [31].…”
Section: Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…The new view on ECs is timely, as, across manufacturing industries, there has been a widespread shift in the approach to manufacturing, from mass production to mass customization [32]. This new approach has been embraced by manufacturers because of the need to make continuous improvements in order to create competitive products [31].…”
Section: Engineeringmentioning
confidence: 99%
“…An example of design changes may take the form of introduction of new options or packages in a vehicle model. Option change management intersects both manufacturing and design [32]. While there are some differences between design engineering changes and manufacturing engineering changes, the processes for implementing these are similar.…”
Section: Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has suggested that MC can be achieved through practices that are related to modularity (Kincade et al , 2007) or postponement (Li et al , 2006). Some studies have also examined the implementation of MC strategies by combining modularity and postponement (Phelan et al , 2017; Ernst and Kamrad, 2000; Brun and Zorzini, 2009).…”
Section: Introductionmentioning
confidence: 99%